MENGUKUR TINGKAT PENERIMAAN TEKNOLOGI MOBILE APPS DI KALANGAN MAHASISWA DI YOGYAKARTA - Sisnuhadi Sisnuhadi (Jurnal Riset Manajemen dan Bisnis, 2017)
The purpose of this study is to measure the acceptance of mobile apps technology using UnifiedTheory of Acceptance and Use of Technology (UTAUT) in Yogyakarta and its surrounding areas. Thestudy found that constructs such as performance expectancy, effort expectancy, and social influencepositively influence behavioral intention. While facilitating conditions and behavioral intention havepositive impact on use behavior. This study also validated that UTAUT model can be used to measurethe acceptance of mobile apps.Keywords: UTAUT, technology acceptance, mobile apps